Genetic variants affecting cross-sectional lung function in adults show little or no effect on longitudinal lung function decline. Issue 5 (7th February 2017) - John, Catherine; Soler Artigas, María; Hui, Jennie; Nielsen, Sune Fallgaard; Rafaels, Nicholas; Paré, Peter D; Hansel, Nadia N; Shrine, Nick; Kilty, Iain; Malarstig, Anders; Jelinsky, Scott A; Vedel-Krogh, Signe; et al.
Abstract : Background: Genome-wide association studies have identified numerous genetic regions that influence cross-sectional lung function. Longitudinal decline in lung function also includes a heritable component but the genetic determinants have yet to be defined. Objectives: We aimed to determine whether regions associated with cross-sectional lung function were also associated with longitudinal decline and to seek novel variants which influence decline. Methods: We analysed genome-wide data from 4167 individuals from the Busselton Health Study cohort, who had undergone spirometry (12 695 observations across eight time points). A mixed model was fitted and weighted risk scores were calculated for the joint effect of 26 known regions on baseline and longitudinal changes in FEV1 and FEV1 /FVC. Potential additional regions of interest were identified and followed up in two independent cohorts. Results: The 26 regions previously associated with cross-sectional lung function jointly showed a strong effect on baseline lung function (p=4.44×10 −16 for FEV1 /FVC) but no effect on longitudinal decline (p=0.160 for FEV1 /FVC). This was replicated in an independent cohort. 39 additional regions of interest (48 variants) were identified; these associations were not replicated in two further cohorts. Conclusions: Previously identified genetic variants jointly have a strong effect on cross-sectional lung function in adults but little or no effect on the rate of decline of lung function. It is possible that they influence COPD risk through lung development. Although no genetic variants have yet been associated with lung function decline at stringent genome-wide significance, longitudinal change in lung function is heritable suggesting that there is scope for future discoveries.